Micro plastic: an imperceptible threat on Agua Dulce Beach, Chorrillos District - Sánchez Contreras, Leonela Lourdes (2022)
The use of plastics in the world is increasing, but their proper final arrangement is limited. Peru made regulatory efforts to reduce its use; however, they are isolated activities that have not represented a significant change in their management. This study allows to identify the presence of microplastic on one of the busiest beaches of the city of Lima Metropolitana, during the emergency period caused by the SARS- COV-2 pandemic. To achieve the objectives of the research, it has been sampled in high tide and supra-coastal areas, applying the methodology proposed in the Ministry of the Environment's Soil Sampling Guide. This study shows the presence of microplastics, with an abundance of 43 pieces per m2, and found that the predominance of the type of microplastic found is of secondary origin (polystyrene and polypropylene); however, 20.9% correspond to primary microplastics (pellets) whose source could not be determined. Finally, it is indicated that despite restrictions on the state of emergency the number of microplastics per m2 in Agua Dulce Beach between 2019 (40 pieces) and 2020 (43 pieces) increased by 7.5%.